The importance to wildfowl of the reservoirs in England and Wales - Atkinson-Willes, G L (Wildfowl, 1961)
The purpose of this paper is to examine the value of reservoirs from a national viewpoint, and more particularly to assess their possible contribution towards the current programme of wildfowl conservation.